ARCHITECTURE IMPACT IN IMPROVING THE QUALITY OF SERVICES IN RETAIL PHARMACIES: CASE STUDY PRISHTINA, KOSOVO - Arta Jakupi; Arianit Jakupi (Journal of Economic and Social Development (Varaždin), 2017)
Aim of this study is to analyse the performance of the pharmacist and the wellbeing of the patients on the actual pharmacy layout (in retail pharmacies in Pristina, Kosovo) and recognize the modifications that need to be done in architectural design of pharmacies, in improving the quality of care, communication, decrease of the dispensing errors and providing more private spaces to patients. Retail pharmacies are more complex environment as in the same time besides being health care institution are also a retail business environment, therefore there is a need for a more comprehensive analysis regarding the workflow. The mixed methodology has been used, by employing questionaries’ as quantitative method and empirical study of direct observation and interviews as qualitative means. The layout proposals are not envisioned to be implemented as a retail models, but, as ideas to provoke and encourage discussion. Kosovo retail pharmacies are a fast growing market and as such functioning self-sufficiently, which means that they can easily adapt to the local marketplace circumstances and cultural context. It is important for the retail pharmacies to test out the recommendations and challenge its environment in aim of equally maximize productivity and workflow, by keeping incorrectness to a minimum.